Cobalt(II) as an additive inhibiting ammonia escape in carbon capture using ammonia solution. Issue 5 (26th August 2013) - Ma, Shuangchen; Song, Huihui; Chen, Gongda; Wang, Yueli; Zang, Bin
Abstract: In this study investigations were carried out to solve the problem of ammonia escape during carbon capture using an ammonia solution. Cobalt(II) solution with a high co‐ordination number and complex ion dissociation constant with ammonia was selected to carry out inhibition experiments for ammonia slip, and the mechanism was validated by UV absorption spectroscopy. The study showed that Co(II) complexation with free ammonia in the absorbent solution forms [Co (NH3 )6 ] 2+, which can significantly reduce the amount of ammonia escaping, and has no significant effects on the carbon capture process. Combining Co(II) as an additive with a conventional washing device under experimental conditions enables NH3 content of less than 10uL/L, meeting emission standards for ammonia in China.